THE PLURAL MANIA GAME’ ENHANCING YEAR 4 PUPILS KNOWLEDGE IN FORMING PLURAL NOUNS - Muhamad Alif Firdaus Ismail; Tengku Fauziah Binti Tengku Abu Bakar (Proceedings of The ICECRS, 2016)
The title of the research is ‘The Plural Mania Game’: Enhancing Year 4 Pupils’ Knowledge in Forming Plural Nouns. The focus of the research was to enhance the knowledge of plural noun forms among Year 4 pupils by using The Plural Mania Game. This intervention helped by introducing the pupils with all regular forms of plural nouns. The intervention was focusing on the teaching and learning through game. The researcher innovated a ‘bingo’ game into a new game called ‘The Plural Mania Game’ to help the pupils of Year 4 improve their knowledge in forming plural nouns. There were 6 pupils involved with this intervention from Year 4 of Sekolah Kebangsaan A who got the lowest marks from the diagnostic test. The data for this study was collected by using the observation, the result of Pre-Test and Post-Test and interview sessions. Based on the findings of data, it was noted that the participants improved their knowledge in forming plural nouns. The result showed that by using The Plural Mania Game helped the pupils in enhancing their knowledge in forming plural nouns. The researcher would like to suggest for the intervention to be implemented in various language skills in the future.